Analisis Naratif Perempuan Madura dalam Bahan Ajar Bahasa Madura (Jurnal Kajian Media, 2018)
How to preserve culture is to be taught and taught as early as possible to the next generation.The most important period in cultural absorption is adolescence, so it is necessary to involve culture in formal education. Women are important to examine, because women have many rules in her living. As a "mother" who will teach the manners and politeness to her child. Women in folklore are examples from culture to guide life.  The method used in this research is the narrative analysis. This method has three stages:looking for defferences of plot and story, searching for structure in narration and identifying character in Madurese folklore on Madurese Language Lesson Materials. The object of this research is the Madurese Language Lesson Materials and the subject of this research is Madurese women. The results of the analysis of Women in Madurese Language Instruction Materials are described as weak figures despite being present in harsh and difficult life environments, having a high religiosity value and having an adventurous spirit.Keywords: Narative Analysis, Madurese Women, Madurese Language Textbook.